Diabetes mellitus and its impact on mortality rate and outcome in pulmonary embolism. Issue 4 (1st December 2021) - Schmitt, Volker H; Hobohm, Lukas; Sivanathan, Visvakanth; Brochhausen, Christoph; Gori, Tommaso; Münzel, Thomas; Konstantinides, Stavros V; Keller, Karsten
Abstract: Aims/Introduction: In patients with pulmonary embolism (PE), the impact of diabetes mellitus on patient profile and outcome is not well investigated. Material and Methods: The German nationwide inpatient sample of the years 2005–2018 was analyzed. Hospitalized PE patients were stratified for diabetes, and the impact of diabetes on in‐hospital events was investigated. Results: Overall, 1, 174, 196 PE patients (53.8% aged ≥70 years, 53.5% women) and, among these, 219, 550 (18.7%) diabetes patients were included. In‐hospital mortality rate amounted to 15.8%, and was higher in diabetes patients than in non‐diabetes patients (19.8% vs 14.8%, P  < 0.001). PE patients with diabetes had a higher prevalence of cardiovascular risk factors, comorbidities, right ventricular dysfunction (31.8% vs 27.7%, P  < 0.001), prolonged in‐hospital stay (11.0 vs 9.0 days, P  < 0.001) and higher rates of adverse in‐hospital events. Remarkably, diabetes was independently associated with increased in‐hospital mortality (odds ratio [OR] 1.21, 95% confidence interval [CI] 1.20–1.23, P  < 0.001) when adjusted for age, sex and comorbidities. Within the observation period of 2005–2018, a relevant decrease of in‐hospital mortality in PE patients with diabetes was observed (25.5% to 16.8%). Systemic thrombolysis was more often administered to diabetes patients (OR 1.18, 95% CI 1.01–3.49, P  < 0.001), and diabetes was associated with intracerebral (OR 1.19, 95% CI 1.12–1.26, P  < 0.001), as well as gastrointestinal bleeding (OR 1.11, 95% CI 1.07–1.15, P  < 0.001). Type 1 diabetes mellitus was shown to be a strong risk factor in PE patients for shock, right ventricular dysfunction, cardiopulmonary resuscitation and in‐hospital death (OR 1.75, 95% CI 1.61–1.90, P  < 0.001). Conclusions: Despite the progress in diabetes treatments, diabetes is still associated with an unfavorable clinical patient profile and higher risk for adverse events, including substantially increased in‐hospital mortality in acute PE. Abstract : In pulmonary embolism, the impact of diabetes mellitus on outcomes is not well investigated. The present study showed that diabetes mellitus is associated with an unfavorable clinical patient profile of pulmonary embolism patients. Diabetes mellitus affects complications and survival in pulmonary embolism patients negatively.